Ripe for revolution building socialism in the Third World - Friedman, Jeremy Scott (Cambridge Harvard University Press, 2021)
A historical account of ideology in the Global South as the postwar laboratory of socialism, its legacy following the Cold War, and the continuing influence of socialist ideas worldwide
Includes bibliographical references and index.
Keywords: Socialism--Developing countries